2015
DOI: 10.1159/000441042
|View full text |Cite
|
Sign up to set email alerts
|

Renal Pseudoaneurysm after Flexible Ureterorenoscopy - An Unusual Complication

Abstract: Pseudoaneurysm following flexible ureterorenoscopy has not been reported so far. The etiology remains unclear as high intra-renal pressure, direct laser damage and damage through stiff guidewire puncture had all been avoided. We like to share this case to make urologists aware of this unusual complication and discuss possible causes and therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…RAP is a pulsatile hematoma formed by blood outflow from the rupture of the renal artery wall and is wrapped by perirenal soft tissue ( 5 ). The wall of an RAP tumor is not a real blood vessel wall but a cystic wall formed by the organization of tissue around the hematoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RAP is a pulsatile hematoma formed by blood outflow from the rupture of the renal artery wall and is wrapped by perirenal soft tissue ( 5 ). The wall of an RAP tumor is not a real blood vessel wall but a cystic wall formed by the organization of tissue around the hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…If an inappropriate guide wire with hard or poor flexibility is chosen, the wire may damage the kidney. However, with the development of technology and materials, super-slippery guide wires have appeared, and the possibility of kidney damage caused by guide wires is lessened ( 5 ); however, they cannot be completely avoided. This may be related to the improper use of the guide wire during the operation or the pathological changes of the kidney itself.…”
Section: Discussionmentioning
confidence: 99%
“…Urothelial mucosal damage or cavitation bubbles were suspected. Recently, Durner et al [ 13 ] reported the case of a patient who underwent bridge therapy for underlying disease status after mitral valve replacement. No notable complications were observed during the procedure, but the patient developed macrohematuria after resuming anticoagulant therapy with low-molecular-weight heparin.…”
Section: Discussionmentioning
confidence: 99%
“…While the risk of rupture is low, it is associated with high mortality rates reaching 80 % in reported cases and the risk of bleeding increases if the size of the pseudoaneurysm >2cm 3 . Renal artery pseudoaneurysms have been reported in various clinical scenarios, including blunt renal trauma, surgery, percutaneous procedures, and spontaneously secondary to inflammatory or neoplastic processes within the kidney 4 . Patients typically present with flank pain, haematuria or unexplained anemia, although many can be asymptomatic.…”
Section: Discussionmentioning
confidence: 99%